Analisa penyalahgunaan social crowdfunding - Hutari Dwi Putri, Felia; Sita Devi, Novianita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Social crowdfunding is fundraising is done voluntarily without any reward. If not properly supervised, this activity can be abused by irresponsible parties. For example, the Cak Budi case in 2017, which used the proceeds from social fundraising not in line with its original purpose. Departing from this case, this study aims to analyze the background of the case and the response from the authorities, as well as to find out how to respond to the case. The research was conducted using descriptive qualitative methods based on news platforms and literature reviews. Based on the results of the analysis in this case, fundraising was only done by individuals, who raised funds through their own personal accounts. The total funds that Cak Budi has collected from 2016-2017 are Rp. 1,066,256,646 which is used for personal purposes. The response from the OJK itself was quite sad, the OJK seemed to be hands off because this fundraising activity was carried out through Cak Budi's personal account. With the occurrence of the Cak Budi case, most people have started to open their eyes about fundraising by a community or individual whether using a platform that collaborates with the authorities in operating a crowdfunding platform.